Current Diet Practice: Intermittent Fasting - İbrahim Hakkı Çağıran (Ebelik ve Sağlık Bilimleri Dergisi)
Obesity is defined as a condition characterized by abnormal or excessive fat accumulation that poses a risk to health. Various behavioral changes include current dietary practices. One of the contemporary dietary approaches, intermittent fasting. Intermittent fasting refers to the cycle between periods of eating and fasting. This review article aims to examine the potential effects of intermittent fasting on health. The study included randomized controlled trials (RCTs) conducted between 2013 and 2024. In the study, a total of 20 different articles were included, examining 1667 participants. Intermittent fasting holds promise for the management and alleviation of symptoms of various non-communicable diseases such as obesity, type-2 diabetes, and metabolic syndrome. While current research suggests that intermittent fasting has beneficial effects on human health, including improved metabolic health and weight management, more clinical studies are needed to better understand this interaction.